Penerapan Modul Elektronik Sigil pada Materi Fluida Dinamis untuk Meningkatkan Kompetensi Pengetahuan dan Minat Belajar Siswa SMA Negeri 1 Baturetno - Harwanti, Afifah; Fauzi, Ahmad; Supurwoko, Supurwoko; Wulandari, Arum (Universitas Sebelas Maret, 2023)
The objective of this research is to: (1) Implement Sigil electronic modules to enhance the knowledge competence of students of Class XI MIPA 5 State High School 1 Baturetno teaching year 2021/2022 on dynamic fluid material, (2) Implements Sigil electronics modules for enhancing the learning interest of students in Class XI of MIPA 5, State High school 1 Buturetno 2021/2022. Class action research (PTK) with models developed by Kemmis and Mc. Taggart was used in this study. Subject of the research is a student of XI grade MIPA 5 State High School 1 Batyretno academic year 2021/2022. Data collection using lifting techniques, tests, interviews, and document studies. Data analysis is quantitative and qualitative analysis. Validation of guides is used to validate the data output of each cycle. The findings of the research are that the application of the electronic module Sigil based on scientific material Dynamic fluids can improve the competence of knowledge and interest in learning students of class XI MIPA 5 State High School 1 Baturetno academic year 2021/2022. Presentation accuracy and class average on knowledge competence increased from 59.38% (class average 69.34) in the pre-cycle phase, increased in cycle I with a top presentation of 93.75% (grade average 83.68), and achieved a 100% (class mean 86.25%) in the cycle II. Presentation of accuration on all four aspects of student learning interests also increased by 3 – 5% from pre cycle, cycle 1, to cycle 2 and has reached the enclosure target.